Reflecting on the Viability of Twitter as Tool in the Postgraduate Supervision Process - Ferreira, J.T. (Frontiers in Education, 2021)
Much has been written on the implementation of Twitter in the higher education environment, but few essays exist on the role that this social media space could potentially fulfill in the postgraduate supervision process. This role is reflected on in this paper. Key literature is reviewed that discusses the essential components of doctorateness: enculturation, communities of practice, and research identity for both student and supervisor that this role could serve. The position of this role in Africa is briefly highlighted. We postulate that Twitter may indeed serve as a valuable and meaningful platform that serves the intersection between the four components of doctorateness.